Propuesta de intervención urbano- arquitectónica del “Museo Municipal” del cantón Guano, en la provincia de Chimborazo - Maldonado Chiriboga, Nicolás Fabricio (2024)
The Guano Municipal Museum is currently facing pressing issues that demand immediate attention. This research project aims to address these problems and improve the museum's internal functioning. The objective is to develop a comprehensive urban-architectural proposal that aligns with the territorial reality, contributing significantly to tourism, social and economic development, and attracting more visitors. This thesis has a comprehensive approach since a project is developed in which the structure of the current museum will be recycled, in addition to the reconfiguration of the urban areas surrounding the museum, such as sports, recreational, and leisure areas, and above all, respect existing heritage monuments, while developing a new museological project in which strategies inspired by architectural references are applied. This approach seeks to preserve the history and culture of Guano while modernizing and revitalizing its cultural infrastructure. The redesign of this museum and its urban environment will improve the accessibility, functionality, and aesthetics of the space, promoting social cohesion and economic and tourist development of the city. The present work projects a technical and objective effort to build an architectural complex for the Guano canton, where this museum allows visitors to enjoy a consistent place that shows the heritage and cultural history of the canton.